Derivation of nomina qualitatis on borrowed stems - Inčiuraitė-Noreikienė, Lina (Vilnius University Open Series, 2022)
This paper investigates the derivation of hybrid derivatives, such as banal-um-as ‘banality’ ← banal-us, -i ‘banal’, that belong to the derivational category of nomina qualitatis. The aim is to find out how different nomina qualitatis with the borrowed stems are from the perspective of derivation, how many derivation steps they consist of. Special attention is paid to the functions of indigenous and borrowed suffixes in the borrowed bases of hybrid derivatives. The study was carried out using the Corpus of the Contemporary Lithuanian Language and the Corpus of Academic Lithuanian. The analysis shows that nomina qualitatis with borrowed stems are not very diverse in terms of derivation, as they are formed with only three indigenous suffixes, i.e. -umas, -ybė and -ystė. The hybrid suffixed -umas and -ybė derivatives are usually derived from adjectives, whereas the suffixed -ystė derivatives are usually derived from nouns. Derivatives with borrowed stems commonly consist of two derivation steps. In morphologically decomposable correlative derivatives borrowed suffixes are suggested to be synchronically regarded as derivational (form-al-us, -i ‘formal’ ⇠ form-a ‘form’).
Keywords: Lithuanian; hybrid derivatives; correlative derivatives; borrowings; derivation steps; derivational suffix; adaptational suffix